Potent and Quick Responses to Conspecific Faces and Snakes in the Anterior Cingulate Cortex of Monkeys - Konoike, Naho; Iwaoki, Haruhiko; Nakamura, Katsuki (Frontiers in Behavioral Neuroscience, 2020)
Appropriate processing of others’ facial emotion is a fundamental ability of primates in social situations. Several mood and anxiety disorders such as depression cause a negative bias in the perception of facial emotions. Depressive patients show a decrease of activation in the perigenual portion of the anterior cingulate cortex (ACC) and an increase of activation in the amygdala. However, it is not known whether neurons in the ACC have a function in the processing of facial emotions. Furthermore, the existence of predators in their vicinity is life-and-death information for monkeys. In the present study, we recorded the activity of single neurons from the monkey ACC and examined the responsiveness of the ACC neurons to various visual stimuli including monkey faces, snakes, foods, and artificial objects. About one fourth of the recorded neurons showed a significant change in activity in response to the stimuli. The ACC neurons exhibited very high selectivity to certain stimuli, and more neurons exhibited the maximal response to monkey faces and snakes than to foods and objects. The responses to monkey faces and snakes were faster and stronger compared to those to foods and objects. Most of the neurons that responded to video stimuli responded most strongly to negative facial stimuli, threat and scream. The response characteristics of the ACC neurons were similar to those of the amygdala neurons. Most of the responsive neurons were located just above or anterior to the genu of the corpus callosum, that is, the perigenual portion of the ACC, which has a strong mutual connection with the amygdala. These results suggest that the perigenual portion of the ACC collaborating with the amygdala forms the neural network underlying emotional information processing, especially for negative life-and-death information such as screaming faces and snakes.